High-Resolution Bathymetry Mapping of Water Bodies: Development and Implementation - Coggins, Liah X.; Ghadouani, Anas (Frontiers in Earth Science, 2019)
Traditionally, bathymetry mapping of ponds, lakes, and rivers have used techniques which are low in spatial resolution. Waste stabilisation ponds (WSPs) are utilised worldwide for wastewater treatment, and throughout their operation require periodic sludge surveys. Sludge accumulation in WSPs can impact performance by reducing the effective volume of the pond, and altering the pond hydraulics and wastewater treatment efficiency. Traditionally, sludge heights, and thus sludge volume, have been measured using techniques such as the 'sludge judge' and the 'white towel' test. Both of these methods have low spatial resolution, are subjective in terms of precision and accuracy, are labour intensive, and require a high level of safety precautions. A sonar device fitted to a remotely operated vehicle (ROV) can improve the resolution and accuracy of sludge height measurements, as well as reduce labour and safety requirements. This technology is readily available; however, despite its applicability, it has not been previously assessed for use on WSPs. This study aimed to design, build, and assess the performance of an ROV to measure sludge height in WSPs. Profiling of several WSPs has shown that the ROV with autonomous sonar device is capable of providing bathymetry with greatly increased spatial resolution in a greatly reduced profiling time. To date, the ROV has been applied on in excess of 400 WSPs across Australia, several large lakes, stormwater retention ponds, river beds, and drinking water reservoirs. ROVs, such as the one built in this study, will be useful for not only determining sludge profiles, but also in calculating sludge accumulation rates and in evaluating pond hydraulic efficiency. As demonstrated, this technology is not limited to application in wastewater management, with the potential for wider application in the monitoring of other small to medium sized water bodies, including reservoirs, lakes, channels, recreational water bodies, river beds, mine tailing dams and commercial ports.